Perancangan Filament Extruder pada Mesin Pengolah Sampah Plastik Terintegrasi “Creatics” Menggunakan Metode TRIZ dan AHP - Aprilia Tri Purwandari; Dicky Sumantri; Niken Parwati; Ahmad Juang Pratama (Universitas Al Azhar Indonesia, 2022)
3D printer technology is being widely used in various manufacturing industries. 3D printers can produce three-dimensional products made of plastic sheets with a certain diameter called filaments. 3D printer filaments that are widely used are made of Acrylonitrile Butadiene Styrene (ABS) plastic. The purpose of this research is to develop a Creatics plastic waste processing machine to produce products in the form of filaments that can be used as materials in 3D printers, so that they have more economic value and are environmentally friendly. Creatics machine is an integrated plastic waste processing machine that converts plastic waste into recycled products. In this study, the Teorija Rezhenija Izobretatelskih Zadach (TRIZ) method is used as a product development method to determine product specifications that are able to generate new ideas by eliminating contradictions and using innovative principles that can produce creative solutions. In the process of selecting alternative concepts, the Analytical Hierarchy Process (AHP) decision-making method is used. The results obtained by the TRIZ method are important parameters and need to be prioritized in designing a filament extruder, namely product reliability, energy use from moving objects, and product strength. The product design chosen based on the AHP method is a filament extruder made of stainless steel to be resistant to rust and utilizes the fan in the filament cooling process.Keywords - AHP method, Creatics machine, Filament extruder, Plastics waste, TRIZ method